A Bronze Age burial ground at Longniddry, East Lothian - Baker, Louise; Henderson, David (Proceedings of the Society of Antiquaries of Scotland, 2004)
Rescue excavation of human remains was carried out at Evergreen, Longniddry, prompted by a chance discovery by workmen. Three crouched inhumations were found, one of which was in a cist. The disturbed and disarticulated remains of two further individuals were also identified. The burials were associated with a concentration of stones and pebbles which may have been the remains of a cairn. Radiocarbon dating yielded dates of 1690 to 1310 cal BC at 2-sigma range. Other burials identified during previous excavations indicate these burials are part of a more extensive Bronze Age burial ground.